3R System Waste Management Planning Model in Bengkulu University Environment - Pandu Imam Sudibyo Adib; Rahmat Nursalim; Eko Sumartono (Perkumpulan Dosen Muda (PDM) Bengkulu, 2021)
Problems of management trash at campus environment of Bengkulu University (UNIB), up to now not yet been planned well and correctness. One of way planning management of trash is by compiling its model of it so that handling of trash a period to coming of can overcome better. Movement which emerge as solution problems of management of environmental trash on campus is movement of eco- campus. Existing trash at campus environment still of resource potency if can be managed better. Organic trash admit of to be used for the raw material of compost, while unorganic trash can be recycled, to be sold or re-used for other usefulness. Management system 3 R ( reduce, and reuse of recycle), have very popular to be applied in area campus environment of UNIB. To apply the system, needed data of amount of arising trash and its type in all existing building (which have been used) campus environment of UNIB. Method Perception to arising trash exist in campus environment of UNIB, used by procedure as which is presented in SNI 3242-2008. Collectively pursuant to measurement the amount of yielded trash volume from all building exist in University environment of Bengkulu equal to 10.402,65 litre/ day while existing accomodation capacities equal to 25.185 litre/ day.25.185,00 litre/ day. Volume mean of transportation 5.250,00 litre/ day. Amount of organic trash equal to 193, 48 kg/ day and unorganic trash equal to 175,60 kg/ day. Estimation assess sale from arising trash which admit of to be used and recycled is Rp 5.226.225,- per month or Rp 62.714.700,- per year.